PERAN GURU DALAM MENGATASI DAMPAK PENGGUNAAN GADGET TERHADAP PERKEMBANGAN SOSIAL ANAK USIA DINI - Sahara, Aminatul; Gina Alya Rizki; Yanna Nirmala; Adrias Adrias; Chandra Chandra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The increasing use of gadgets among young children, in tandem with the rapid development of digital technology, has become a serious concern due to its potential to affect children’s social development, particularly in terms of face-to-face interaction and empathy. This study aims to analyze the role of Early Childhood Education (PAUD) teachers in addressing and minimizing these impacts. The method used is a literature review with a critical analysis of various national and international journals relevant to the research topic. The results indicate that ECE teachers play a crucial role as guides, observers, and facilitators of children’s social interactions, as well as role models, digital literacy educators, and collaborative partners for parents in managing gadget use. Fulfilling these roles requires adequate pedagogical competencies and the ability to adapt to dynamic technological advancements. This study concludes that strengthening the role of teachers in addressing the impacts of gadget use requires collaborative support among schools, families, and education policymakers. The implications of this study emphasize the importance of enhancing teachers’ competencies through digital literacy training and the development of learning strategies that support the social development of young children.